If you take a mouse to school - Numeroff, Laura Joffe; Bond, Felicia (New York : Laura Geringer Books, 2002)
Describes the mountain of mischief a mouse could get into--in science class, reading class, and playtime, for example--if he came along to school.
Book Links (A.L.A.).
School Library Journal.
Wilson's Children.
2.7
K-3
Keywords: Mice -- Fiction; Schools -- Fiction; Mice -- Fiction; School stories